Предмет: Алгебра,
автор: Дмитрий771
27-(x-2)^3
(m+1)^3+64
Ответы
Автор ответа:
0
( А + в) ^ 3 = а^3 + 3а^2 в + 3 ав^2 + в^3
пользуемся этой формулой и
27 -( х^3 - 6 х^2 + 12х - 8) = 27 - х^3 + 6х^2 - 12х + 8
= - х^3 + 6х^2 + 35
м^3 + 3м ^2 + 3 м^2 + 1 + 64= 4 м^3 + 3м^2 + 65
пользуемся этой формулой и
27 -( х^3 - 6 х^2 + 12х - 8) = 27 - х^3 + 6х^2 - 12х + 8
= - х^3 + 6х^2 + 35
м^3 + 3м ^2 + 3 м^2 + 1 + 64= 4 м^3 + 3м^2 + 65
Похожие вопросы
Предмет: Физика,
автор: CatPersLife
Предмет: Беларуская мова,
автор: Аноним
Предмет: История,
автор: Dimoooon0806
Предмет: Биология,
автор: kiselewanastia